Assessment of Geo-Environmental and Ethno-Cultural tourism of Jampui Hill Tripura through perceptual approach - Mitra, Saptarshi; Hrangkhawl, Jony; Roy , Stabak (Turizam, 2023)
Infrastructure is an integral part of tourism. The worldwide tourism economy experienced a massive hike post covid period with special reference to Geo-tourism. India is rich in culture and natural resources, and the North-eastern part of India is so enriched that it potentially carries diversified tourism in all eight states of this region. But tourism infrastructure is facing a serious issue in this country, especially in Tripura. The present study illustrates the Geo-tourism infrastructure and assesses the tourists' perceptions at Jampui Hill. The socio-economic class of the tourists has been defined using the modified Kuppuswamy scale, and the Index of Satisfaction (IS) has been measured using the five-point Likert Scale method. SCOT and Qualitative analyses were also done to determine the possible and negative transition of the tourism economy at Jampui hill. The study reveals that tourists aren't fully satisfied with the available tourist infrastructure and describes very few tourist activity areas at Jampui hill spot. A sustainable tourism approach should be adopted to decrease the negative impact and stimulate the positive development of the tourism economy at Jampui hill.
Keywords: Kuppuswamy scale, Satisfaction Index, Geospatial technique, SCOT